Case Study : Faiza Sdn. Bhd / Afnan Syahmi Mohd Nazri - Mohd Nazri, Afnan Syahmi (2021)
Syarikat FAIZA was founded in 1982 and its major business is retail activity. The Syarikat FAIZA was formally established as a member under Syarikat FAIZA Sdn. Bhd. (SFSB). In 1997, Syarikat was invested in risk capital by Padiberas Nasional (BERNAS).At the end of the 1990s, customers began to analyse the processing and other characteristics of food goods more attentively. At this time, the firm was introduced by Kartanaka, South India to a unique class of medicinal grade rice. It was "Ponni" herbal rice. With a view to a million blows, SFSB rapidly identified rice users' fundamental advantages in their diet with "ponni." Ponni rice is now available across Malaysia under the brand name Taj Mahal.As a result, Taj Mahal has had a significant influence on customer demand for other SFSB rice products such as Basmathi, Fragrant rice, Thai Super Special, and Local rice.